UNODA Occasional Papers No.10: Verifying Non-Proliferation & Disarmament Agreements Today, March 2006 - Bureau des affaires du désarmement des Nations Unies (United Nations, 2003)
The Department for Disarmament Affairs, renamed United Nations Office for Disarmament Affairs in 2007 (UNODA) Occasional Papers is a series of ad hoc publications presenting, in edited form, papers or statements made at meetings, symposiums, seminars, workshops or lectures that deal with topical issues in the field of arms limitation, disarmament and international security. They are intended primarily for those concerned with these matters in Government, civil society and in the academic community.